Weighing of Performance Indicator Components National Road Condition Program in Maluku Province - Burhanuddin Hasri; Buri Hartanto Susilo; Hamkah Hamkah (Eduvest - Journal of Universal Studies, 2025)
The Program Performance Indicator (IKP) stipulated in the Guidelines for the Road and Bridge Sector No.07/P/BM/2021 is an indicator to measure the fulfillment of the level of road network services. The IKP consists of four components where the IKP value is the average value of the four components. The four components of the IKP are unevenness (IRI), pavement surface condition (PCI), remaining pavement life (RSL), and drainage effectiveness with the weight of each component set in the guidelines, namely IRI 60%, PCI 10%, RSL 15%, and drainage effectiveness 15%. The weight can also be adjusted to the specifics of each Center or Province. This study aims to examine the components of IKP in West Papua and West Java Provinces. The research was conducted using the Analytical Hierarchy Process (AHP) method to obtain a ranking of each IKP component. The results of the study were obtained that the weight of the IKP component based on the guidelines could be accepted and applied to the review area, except for the weight of the PCI for Maluku Province where less than 75% of respondents stated that it was appropriate. The weight of the components obtained based on the AHP analysis for the Maluku region is IRI 28%, PCI 27%, RSL 23%, and drainage effectiveness 22%. The results of the study can be considered as a reference for the preparation of component weights for other provinces in Indonesia.